Ferroptosis in NAFLD: insights and the therapeutic potential of exercise - Chang Li; Dongkun Deng; Qingfeng Jiang; Jiaming Shi; Lin Xu; Yufei Liu (Frontiers in Medicine)
Ferroptosis, a distinct form of non-apoptotic cell death driven by iron accumulation, has garnered significant attention in recent years. Emerging evidence suggests that ferroptosis in hepatocytes may serve as a pivotal trigger in the pathogenesis of non-alcoholic fatty liver disease (NAFLD). Importantly, inhibiting ferroptosis has shown promising potential in slowing the progression of NAFLD. Concurrently, exercise, a cornerstone in the prevention and management of chronic diseases, plays a critical role in regulating disease progression. As such, the modulation of ferroptosis through exercise represents a promising avenue for developing innovative therapeutic strategies. This review aims to systematically elucidate the conceptual framework and molecular mechanisms underlying ferroptosis, with particular emphasis on its pathophysiological role in NAFLD. We have systematically summarized the effects of exercise on ferroptosis regulation through multiple molecular mechanisms, including upregulation of antioxidant defense systems via activation of NRF2, GPX4, and SLC7A11 signaling pathways; and modulation of iron metabolism through FPN-mediated iron homeostasis regulation. These findings not only provide valuable insights into the molecular basis of exercise-induced protection against ferroptosis-mediated cellular damage but also offer novel perspectives for future investigations into exercise-based interventions for NAFLD management. This work thereby contributes to the advancement of therapeutic strategies in the field of metabolic liver diseases.